Factors that Influence the Risk of Red Chili Production in Taraju District, Tasikmalaya Regency - Candra Nuraini; Irma Amelia Sukma; D.Yadi Heryadi; Januar Arifin Ruslan (International Journal of Economics, Business and Innovation Research, 2024)
The red chili commodity has a high farming risk. Therefore, it is necessary to carry out an analysis regarding the factors that influence the risks of chili farming. This research aims to analyze the factors that influence the productive risk of red chili farming. This research was conducted in Banyuasih Village, Taraju District, Tasikmalaya Regency, West Java. The data used are primary and secondary. The sampling technique used a proportional random sampling system with a sample size of 37 people. The analysis method used was the Just and Pope method, with a disturbance error/production risk approach regressed on the independent variables using the Ordinary Least Square/OLS method. The results showed that urea, seeds, land, labor, and manure significantly influenced the risk of red chili production. So, using production risk factors for each addition of urea fertilizer and seeds can reduce production risk, and each addition of land, labor, and manure can reduce the risk of red chili production.